PEMANFAATAN TIPE DAN TAKARAN PELATIHAN YANG TEPAT DALAM PENINGKATAN KEMAMPUAN KOMPONEN BIOMOTORIK ATLET - Tampi, Siane Maria (Ordik, 2013)
It is found that some trainers, in training their athletes, have still not understood the type of training and the appropriateness of the portion as well as the appropriateness to the type of the sport. This article is aimed at giving descriptions of the appropriate type and portion of training is one chosen based on the specification movement of the sport type. While the training amount is intensity, volume, duration and frecuency of an activity done by an athlete in a period of time to enhance the fuctional abilities of the body organ in order to be able to adapt to the changes appropriate to the goal of the training.   Keywords: tipe, takaran pelatihan, peningkatan, komponen, biomotorik dan atlet.